The future of aviation - Givoni, M; Banister, D (Transport Select Committee, 2009)
Due to its central role in the UK air transport system the future of Heathrow holds the key to the future of UK aviation and for meeting the government goals to secure air transport contribution to the economy along side its accessibility benefits to the UK regions while lowering its adverse impact on the environment.